Unsteady Flow Through a Porous Medium Due to Non-coaxial Rotations of a Porous Disk and a Fluid at Infinity Subjected to a Periodic Suction - M. Guria (International Journal of Applied Mechanics and Engineering, 2018)
The unsteady flow of a viscous incompressible fluid due to non-coaxial rotations of a porous disk and a fluid at infinity subjected to a periodic suction through a porous medium has been studied. The velocity field, shear stresses are obtained in closed form. The variations of primary and secondary velocities for different values of non dimensional parameters are depicted in figures.